Faktor yang Berhubungan dengan Kejadian Low Back Pain pada Pekerja Pembuat Batu Bata (cross sectional study) - Anggi Isnani Parinduri; Fadlilah Widyaningsih; Irmayani Irmayani; Rosita Ginting; Raisha Octavariny (Jurnal Riset Hesti Medan, 2021)
Low back pain is one of the musculoskeletal disorders caused by repetitive movements and poor body activities. Almost 80% of the population has experienced low back pain in their life cycle. Low back pain is one of the most common complaints related to a job. The purpose of this study was to analyze the factors associated with the incidence of low back pain in brick-making workers. This research method is a quantitative research using a cross sectional design. The population is 38 people with purposive sampling technique sampling. Bivariate analysis using Chi Square test. The results showed that from 38 workers there were 25 people who experienced low back pain. The results of the chi square test showed that there was a relationship between age and low back pain (p = 0.001) and there was a relationship between years of service and low back pain (p = 0.0001). It is recommended that workers always apply ergonomics principles in doing their work so as to reduce the level of risk of low back pain, for brick industry owners it is recommended to re-design work facilities and add mechanical aids to eliminate manual hazards, as well as suggestions for related agencies should make policies and supervision of problems in the informal sector, especially the brick industry.